2022
DOI: 10.1371/journal.pdig.0000158
|View full text |Cite
|
Sign up to set email alerts
|

Is artificial intelligence capable of generating hospital discharge summaries from inpatient records?

Abstract: Medical professionals have been burdened by clerical work, and artificial intelligence may efficiently support physicians by generating clinical summaries. However, whether hospital discharge summaries can be generated automatically from inpatient records stored in electronic health records remains unclear. Therefore, this study investigated the sources of information in discharge summaries. First, the discharge summaries were automatically split into fine-grained segments, such as those representing medical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…When examining whether AI can generate discharge summaries from inpatient records, it was shown that the origins of information contained in a discharge summary is varied and 39% of the information comes from the inpatient record, with 11% deriving from the physician’s memory. 20 This raises concerns with the feasibility of AI involvement in clinical communication, which aligns with the data governance issues raised by Patel and Lam. 16 They discussed the potential of using ChatGPT to generate discharge summaries and, while they recognised the benefits of automation, standardisation, and efficiency, they also highlighted that errors are frequent, and a minor error could have catastrophic consequences in the clinical environment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…When examining whether AI can generate discharge summaries from inpatient records, it was shown that the origins of information contained in a discharge summary is varied and 39% of the information comes from the inpatient record, with 11% deriving from the physician’s memory. 20 This raises concerns with the feasibility of AI involvement in clinical communication, which aligns with the data governance issues raised by Patel and Lam. 16 They discussed the potential of using ChatGPT to generate discharge summaries and, while they recognised the benefits of automation, standardisation, and efficiency, they also highlighted that errors are frequent, and a minor error could have catastrophic consequences in the clinical environment.…”
Section: Discussionmentioning
confidence: 97%
“… 16 They, like Ando et al , have recommended that any future AI involvement will always need human oversight to minimise patient safety risks as well as providing more personalised information where needed. 16 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining ways to standardize how teach-back is implemented and delivered to patients may achieve better results. Artificial intelligence may have a future role in a patient’s discharge process (Ando et al, 2022; Patel & Lam, 2023). Using artificial intelligence models may communicate with patients in a style or level that is better understood.…”
Section: Discussionmentioning
confidence: 99%
“…The authors, therefore, concluded that AI's can only be a tool used as part of the discharge summary writing process. 26 …”
Section: Chatgpt For Healthcare Communicationmentioning
confidence: 99%